The effects of real exchange rate shocks in an economy with extreme liability dollarization - Ola Melander (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
This paper studies the effects of real exchange rate depreciation in an economy with extreme liability dollarization using vector autoregression (VAR) methods. Bolivia's extreme liability dollarization makes it an interesting case for empirical testing of the contractionary-depreciations hypothesis. In contrast to the previous contractionary-depreciations literature, the paper uses identification assumptions which are inspired by modern macroeconomic theory and common in the empirical VAR literature on the effects of monetary policy. I find that a real exchange rate depreciation has negligible effects on output, since a contractionary balance-sheet effect on investment is counteracted by the standard expansionary effect on net exports. Furthermore, I find that a real depreciation has inflationary effects. A key finding is that the identification assumptions used in this paper gives more reasonable results than alternative assumptions used in the previous literature.
Keywords: E44; F41; G15; 330; Real exchange rate; VAR; liability dollarization; balance sheet effects; contractionary depreciation; Kaufkraftparität; VAR-Modell; Währungssubstitution; Zahlungsbilanz; Neue Makroökonomik offener Volkswirtschaften; Bolivien